2021
DOI: 10.1111/inr.12692
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ core emergency competencies for COVID‐19 in China: A cross‐sectional study

Abstract: Aim To investigate nurses’ core emergency competencies for handling the coronavirus disease‐19 (COVID‐19) and analyse the factors associated with those competencies. Background COVID‐19 has become a major global public health event. Nursing staff have played an important role in COVID‐19 prevention and control. Understanding their emergency competencies for handling COVID‐19, and the potential disadvantages will help governments to develop targeted training policies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…These events include technological advances ( Nes et al, 2021 ), changes in professional nursing practice ( Shun, 2021 ), and the diversity of patients and their belief systems (Ogbulo et al, 2018). The COVID-19 pandemic has affected how nurses perceive nursing care practice ( Chen et al, 2020 ) and their professional value system ( González-Pando et al, 2021 ), and competencies ( Li et al, 2021 ). In their study of nurses working with COVID-19-infected patients, Alloubani et al (2021) identified three themes about nurses' ethics and morality.…”
Section: Introductionmentioning
confidence: 99%
“…These events include technological advances ( Nes et al, 2021 ), changes in professional nursing practice ( Shun, 2021 ), and the diversity of patients and their belief systems (Ogbulo et al, 2018). The COVID-19 pandemic has affected how nurses perceive nursing care practice ( Chen et al, 2020 ) and their professional value system ( González-Pando et al, 2021 ), and competencies ( Li et al, 2021 ). In their study of nurses working with COVID-19-infected patients, Alloubani et al (2021) identified three themes about nurses' ethics and morality.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic challenged frontline nurses’ personal and professional lives; they were at risk of the COVID-19 disease due to daily nursing care and direct contact with patients, underwent heavy workload, and faced problems in their daily lives [ 33 , 34 ]. A study in China indicated that nurses perceived the knowledge of COVID-19 well, but most of them lacked work experience in isolation and coronavirus wards, which in turn affected their clinical competences [ 35 ]. Since nursing competence plays an important role in the quality of nursing services, particularly in crises, it is crucial to evaluate clinical competency and its correlates during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the most important transversal soft skills were coping with stress and emotional management, followed by communication and interpersonal relationships. Li et al (2021) investigated the core emergency capabilities of 2570 nurses in dealing with COVID‐19 and analysed the factors related to these capabilities. In the study, nearly half of the nurses are from the department of internal medicine.…”
Section: Resultsmentioning
confidence: 99%